Co-verbal gestures among speakers with aphasia: Influence of aphasia severity, linguistic and semantic skills, and hemiplegia on gesture employment in oral discourse - Kong, Anthony Pak-Hin (J Commun Disord, 2015)
The use of co-verbal gestures is common in human communication and has been reported to assist word retrieval and to facilitate verbal interactions. This study systematically investigated the impact of aphasia severity, integrity of semantic processing, and hemiplegia on the use of co-verbal gestures, with reference to gesture forms and functions, by 131 normal speakers, 48 individuals with aphasia and their controls. All participants were native Cantonese speakers. It was found that the severity of aphasia and verbal-semantic impairment was associated with significantly more co-verbal gestures. However, there was no relationship between right-sided hemiplegia and gesture employment. Moreover, significantly more gestures were employed by the speakers with aphasia, but about 10% of them did not gesture. Among those who used gestures, content-carrying gestures, including iconic, metaphoric, deictic gestures, and emblems, served the function of enhancing language content and providing information additional to the language content. As for the non-content carrying gestures, beats were used primarily for reinforcing speech prosody or guiding speech flow, while non-identifiable gestures were associated with assisting lexical retrieval or with no specific functions. The above findings would enhance our understanding of the use of various forms of co-verbal gestures in aphasic discourse production and their functions. Speech-language pathologists may also refer to the current annotation system and the results to guide clinical evaluation and remediation of gestures in aphasia.